Rubber Rumours an Assessment of Processes of Change In an Indonesian Frontier Area - Woensdregt, Wietse (Departement of Communication and Community Development, 2014)
The major focus of international media towards processes of change in frontier are asison the victim isation of the indigenous people.They are subject to macro changes and can only follow along. In Kiham Batang, a village in Central Kalimantan, Indonesia,the villagers are coping with recent developments in the area due to the establishment of a logging concession. The concession owners, PTSBK, have opened up the area for the villagers to engage with new types of livelihoods like gold mining and rubber cultivation. At the same time, foreign traders create a high demand for rare animals that can be hunted close to the village. Due to a high demand for arable land and a highland scarcity, the villagers engage in a resource frenzy toen sure their place in the future.This paper argues that structural changes and agency of villagers are both responsible for change,and that rumours and future fantasies play an active role in the decision making of the villagers to engage in new market opportunities. © 2014 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keywords: Kalimantan, rural transformation, rumours, gold mining[How to Cite: Woensdregt, W. (2014). Rubber Rumours an Assessment of Processes of Change In an Indonesian Frontier Area.Journal Of Rural Indonesia, 2(1), 13-30. Retrieved from http://ejournal.skpm.ipb.ac.id/index.php/ruralindonesia/article/view/291]